Medical Therapy of Sarcoidosis - Baughman, Robert P.; Lower, Elyse E. (Seminars in Respiratory and Critical Care Medicine, 2014)
For treatment of sarcoidosis, one should develop a long-term management plan. Factors to be considered include the organ involvement and severity of symptoms. Different organ manifestations may require different treatments. Intensity of treatment is usually based on severity of disease or potential for organ failure or death. Glucocorticoids are quite effective as initial therapy for most forms of sarcoidosis. However, the toxicity associated with long-term treatment often leads to the use of alternative treatments. These include cytotoxic agents such as methotrexate, biologic agents such as the antitumor necrosis factor antibody infliximab, and other anti-inflammatory drugs such as hydroxychloroquine. In some cases, anti-inflammatory drugs may not help. Examples include pulmonary hypertension and fibrosis.
Keywords: sarcoidosis; medical therapy; glucocorticosteroids; immunosuppressive agents; TNF inhibitors